Pembelajaran Problem Based Lerning (PBL) dengan Nilai Ke-Islaman dan Self-Efficacy; Dampak dan interaksinya terhadap Kemampuan Berpikir Kritis - Fredi Ganda Putra; Santi Widyawati; Isna Lutfinatun Nabila (JEMS: Jurnal Edukasi Matematika dan Sains, 2021)
The purpose of this study was to determine the impact and interaction between Problem Based Learning integrated Islamic values and students' self-efficacy levels on their mathematical critical thinking skills. This type of research is Quasy Experimental Design. There are 2 data collection techniques used in the study, namely: questionnaires and tests. The hypothesis test used is two-way analysis of variance of different cells. The results showed that: 1) mathematical critical thinking skills with integrated Problem Based Learning Islamic values are better than using conventional learning; 2) the mathematical critical thinking ability of students who have high self-efficacy is better than having moderate or low self-confidence; 3) there is no interaction between the application of the Integrated Problem Based Learning model of Islamic values and students' self-efficacy on critical thinking skills and low self-efficacy.